Modern Approaches to Raynaud’s Phenomenon: Pathophysiology, Treatment, and Emerging Therapies - Review of the literature - Madura, Paulina; Gawin, Konrad; Zawiślak, Wiktoria; Ignasiak, Anita; Cisowski, Michał; Dąbrowska, Maria; Rychlica, Kacper; Cholewińska-Rychlica, Jolanta; Mrozik-Gałecka, Daria (Quality in Sport, 2026)
Raynaud’s phenomenon (RP) is a multifactorial vasospastic disorder characterized by episodic digital ischemia, commonly triggered by cold exposure or emotional stress. RP may present as primary (idiopathic) or secondary, the latter often associated with systemic sclerosis or other connective tissue diseases and carrying a higher risk of complications such as digital ulcers and tissue loss. This narrative review aims to synthesize current evidence on the pathophysiology, clinical manifestations, and management strategies for RP, including non-pharmacologic interventions, pharmacologic therapies, surgical approaches, and adjunctive nutraceuticals. Results Non-pharmacologic measures, including trigger avoidance, temperature management, smoking cessation, and patient education, remain foundational, particularly for primary RP. Calcium channel blockers are first-line pharmacologic agents, reducing attack frequency, duration, and severity. Second-line therapies include phosphodiesterase-5 inhibitors and prostanoids, primarily intravenous iloprost, for refractory or ischemic cases. Endothelin receptor antagonists prevent digital ulcer recurrence in secondary RP. Botulinum toxin injections and surgical interventions, such as digital sympathectomy or angioplasty, may benefit selected patients with severe disease. Adjunctive dietary supplements, including omega-3 fatty acids, Ginkgo biloba and antioxidant vitamins, show biological plausibility but lack high-quality clinical evidence. Across all treatment modalities, high-quality randomized controlled trials remain limited, and standardized outcome measures are inconsistently applied.